Trace Metal Residues in Swimming Warrior Crab Callinectes bellicosus: A Consumption Risk - Marisol Castro-Elenes (Frontiers Media S.A., 2021)
This study was carried out in the Navachiste coastal lagoon, Mexico, surrounded by intensive agricultural and aquaculture activities that cause environmental pollution by the deposition of trace metal residues in the sediments of this coastal lagoon. The trace metals are bioaccumulated by benthic organisms such as the blue swimming warrior crab, Callinectes bellicosus, which inhabits this lagoon and is consumed by humans. Ninety-five C. bellicosus edible tissue samples were collected (April 2014–January 2015). The extraction procedure of the trace metals in edible tissue samples was carried out by acid digestion with nitric acid. Based on the Environmental Protection Agency (EPA) of the United States, two indices were used to measure health risk: the estimated daily intake (EDI) and the target hazard quotient (THQ). The hazard index (HI) was used to calculate the probability of adverse carcinogenic risk and the target hazard quotient per sample (MHI) to calculate the probability of developing a carcinogenic or non-carcinogenic risk. The analysis of variance (ANOVA) showed significant differences among trace metal concentrations (p < 0.01), but all trace metal concentrations in the edible tissues of C. bellicosus were higher than the maximum residual limits (MRLs). The highest EDI was for Zn, Fe, and Cu, showing that the consumption of these crabs might represent health risks. The THQ >1 was for Ni, Zn, Cd, and Cu, and the HI = 16 revealed the risk of C. bellicosus for high-level consumers. The MHI showed that 98% of samples presented a THQ >1, implying a high rate of bioaccumulation of trace metals by the crabs independent of the sampling site in the NAV. The presence of trace metals in the edible tissue of crabs reflects contamination by trace metals, and the indices results mean that the NAV lagoon is constantly polluted with trace metal residues by neighboring agriculture and aquaculture activities. These trace metal residues are being bioaccumulated in the edible tissues of C. bellicosus due to its feeding habits, resulting in a health risk if its consumption is high, including carcinogenic and non-carcinogenic risks.